General contractors' experience using off-site structural framing systems. Issue 1 (18th May 2020) - Killingsworth, John; Mehany, Mohammed Hashem; Ladhari, Hana
Abstract : Purpose: This paper aims to examine general contractors' experiences of using off-site manufactured structural framing systems. This engaged a single-case study using a qualitative methodology to identify expected benefits, actual benefits and challenges of such systems. Design/methodology/approach: A single-case study approach evaluated general contractors' experience of using a manufactured structural framing system. Qualitative data were collated and analyzed from industry domain experts to determine commonalities and thematic thinking. Findings: The study revealed that the reasons behind considering off-site building systems were: accelerating the project schedule, overcoming site constraints and having a better end-product. The top expected benefits were: saving time (schedule), saving cost and improving quality. The top actual observed benefits were: saving erection time, reducing waste generation, reducing project costs, reducing safety risks and improving construction site logistics. The main challenges encountered were: unfamiliarity of different project parties with the off-site framing system, difficulty with reducing the overall project schedule, heavy site logistics and complicated off-site system design and standards requirements. The findings include solutions to overcome the challenges associated with using a manufactured structural system. Research limitations/implications: This paper was a case study and therefore inherently limited in its generalizability. The study was conducted with general contractors in the mountain-west region of the USA. However, the implications of the study may have a broad application, as contractors across the globe seek to find similar solutions to using off-site or manufactured construction methods. Practical implications: Construction labor shortages around the world are forcing the construction industry to find creative solutions to meet the demand for their services. Manufactured or off-site construction methods provide a possible solution to that labor shortage. However, builders need to be aware of the immediate challenges and actual benefits of using a manufactured structural framing system. Social implications: Manufactured structural framing systems have the potential to impact lean and sustainable practices in construction. Reduced waste, reduced on-site man-power requirements, reduced construction schedules and reduced injuries each improve the lives of construction workers and the communities around these buildings. Originality/value: An extensive literature review was performed to guide the design of this case study. Much has been written about off-site construction practices, but there is a significant research gap on the topic of structural framing systems. This study contributes to expanding the knowledge of off-site construction and specifically helps researchers and practitioners understand the challenges and benefits of this systematic approach to construction.